Analisis Intrinsik Tiga Lagu dalam Pembelajaran Bahasa Jerman - Nursida Nursida; Syamsu Rijal; Wahyu Kurniati Asri (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. This research is qualitative descriptive research. The purpose of this study is to find out the intrinsic elements of the song, namely the theme, tone, feelings, and mandate contained in the song. The data sources in this study are primary data and secondary data. The primary data sources are three songs, namely "Stadt der Reichen", "Was hat dich bloβ so ruiniert" by indie band Die Sterne and the song "Wir trafen uns in einem Garten" by musician 2raumwohnung, and secondary data sources, namely information or writing related to the theme of the song. Data collection uses library techniques, which are in the form of reading and recording techniques against research objects. The data obtained is analyzed based on the intrinsic elements of the song. The data obtained is analyzed with content analysis techniques (Content analysis). The results of this study are as follows, intrinsic elements of the song "Stadt der Reichen", themes: social injustice, tone: criticism, feelings: disappointment, mandate: justice in society. Intrinsic elements of the song "Was hat dich bloβ so ruiniert", theme: suffering, tone: questioning, feelings: sadness, mandate: it is not good to harbor sadness too deeply. The intrinsic element of the song "Wir trafen uns in einem Garten", theme: memories, tone: happy, feeling: joy, mandate: memories that make happy should always be remembered. Some aspects of learning in songs such as sentence structure in the form of Prӓsens, Prӓteritum and dativ prepositions, so that the three songs can be an option for german learning in the school. Keywords: German Language, Song, Intrinsic Analysis of Learning.